Artifacts and allegiances : how museums put the nation and the world on display - Levitt, Peggy (University of California Press, 2015)
The bog and the beast: the view of the nation and the world from Stockholm, Copenhagen, and Gothenburg -- The legislator and the priest: cosmopolitan nationalism in Boston and New York -- Arabia and the east: how Singapore and Doha display the nation and the world.